Ideas of Moral and Patriotic Education in the Ukrainian Pedagogical Culture of XVI - XVII Centuries - Olena Hapchenko (Pedagogical Discourse, 2012)
The article deals with the research of the character and content of the process of education of personality in Ukrainian pedagogical culture of XVI - XVII centuries. Attention is accented on the fact that one of its main bases was forming of moral, spiritual man with the developed sense of love to the native land and respect to national spiritual heritage. The special importance education of personality had during the period of cultural and national revival of XVI - XVII centuries.